Faktor-Faktor Yang Berhubungan Dengan Risiko Kejadian Stroke Di Ruang Rawat Inap A di Rumah Sakit Stroke Nasional Bukittinggi Tahun 2017 - Ningsih, Ropika (Menara Ilmu, 2018)
Stroke is a clinical syndrome due to disruption of blood flow to the brain, suddenly ariseand more experienced by patients aged ? 55 years.This research purposes to determine thefactors that are associated with the risk of stroke incidence in the Inpatient Room A atBukittinggi National Stroke Hospital 2017.Type of research used descriptive correlation with Cross sectional studyapproach.Sampling using purposive sampling technique to get a sample of 72 people.Datacollection in this study using questionnaire. Data were analyzed statistically by using chi-squaretest.The results showed that 69.4% were at risk for stroke, 41.7% respondents with age factor,63.9%, with male gender factor, 80.6% with hypertension factor, 86.1%, with diabetes factormellitus, 84.7% with less physical activity factor. (P = 0.001), hypertension (p = 0.000), diabetesmellitus (p = 0.004), smoking (p = 0,000), lack of physical activity (p = 0.472) with risk strokeincidence no relationship.It can be concluded that the factors of age, gender, hypertension, diabetes mellitus,smoking are associated with the risk of stroke incidence except for lack of physical activity. Forthat it is expected to various parties, especially nurses at the National Stroke Hospital ofBukittinggi to perform early detection of risk factors for stroke.It can be concluded that thefactors of age, gender, hypertension, diabetes mellitus, smoking are associated with the risk ofstroke incidence except for lack of physical activity.Keywords :Age factor, gender, hypertension, diabetes mellitus, smoking, lack ofphysical activity, risk of stroke.